Physical activity and pharmacological interventions in reversing stress-induced hippocampal atrophy: An analysis of molecular mechanisms - Pawlak, Paulina; Wojcieszuk, Olaf; Starczewski, Łukasz; Babik, Adrianna; Kamińska, Kamila; Będkowska-Kuśmierek, Matylda; Złotnik, Anna; Krzysztofik, Kinga; Klamka, Antoni; Kawalec, Paulina (Quality in Sport, 2026)
Background: Chronic stress, unlike its acute adaptive form, leads to a persistent disruption of homeostasis and an increasing allostatic load. A central component of the biological response to stress is the activation of the hypothalamic-pituitary-adrenal (HPA) axis, which leads to the release of glucocorticoids, particularly cortisol. The hippocampus, due to its high density of glucocorticoid receptors, becomes one of the main target structures for cortisol action. Its chronic excess becomes neurotoxic to the hippocampal structure and leads to its atrophy. Aim:The aim of this study is to analyze the mechanisms leading to hippocampal damage and to evaluate the clinical evidence regarding the reversibility of these changes through pharmacological and non-pharmacological interventions. Material and methods:The literature review was conducted by searching the electronic databases PubMed and Google Scholar. The search process utilized a combination of the logical operators AND/OR and the following keywords: chronic stress, cortisol, hippocampal atrophy, neuroplasticity, HPA axis, BDNF, physical exercise. Results: Chronic exposure to cortisol leads to dendritic atrophy, loss of synaptic spines, and inhibition of neurogenesis within the hippocampus. Recent reports, however, highlight the key role of the mTORC1 signaling pathway and BDNF expression in reversing these deficits. While psychoplastogens such as ketamine promote rapid synaptic remodeling, regular physical activity facilitates sustained structural adaptations.Conclusions: Hippocampal damage caused by chronic stress is not a completely irreversible process. The transition from a neurotoxic state to structural regeneration is possible through multi-track molecular pathways activated by both modern pharmacotherapy and systematic physical activity. This synergy opens new perspectives in education and sports medicine, aiming at the biological reconstruction of brain structures and improvement of the quality of life.